2022
DOI: 10.1007/s40615-022-01292-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Emotional Labor of Public Health Equity Work: a Mixed Methods Study

Abstract: Background Rectifying historic race-based health inequities depends on a resilient public health workforce to implement change and dismantle systemic racism in varied organizations and community contexts. Yet, public health equity workers may be vulnerable to job burnout because personal investment in the continual struggle against inequality exacts an emotional toll. Our study sought to quantify the presence of emotional labor in public health equity work and better understand its dimensions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Hawkins used the phrase "racism burnout" [7], reflecting that the continuing experience of racism was a reason for the burnout. Indeed, many studies stated that racism is a factor in burnout [169,229,230,347,348].…”
Section: Burnout and Disabled Peoplementioning
confidence: 99%
“…Hawkins used the phrase "racism burnout" [7], reflecting that the continuing experience of racism was a reason for the burnout. Indeed, many studies stated that racism is a factor in burnout [169,229,230,347,348].…”
Section: Burnout and Disabled Peoplementioning
confidence: 99%
“…According to the 2021 Public Health Workforce Interests and Needs Survey, public health employees have increasing levels of stress, burnout, and intent to leave (de Beaumont Foundation, 2022 ). For public health professionals working to advance health equity (hereafter, “health equity professionals”), the struggle against structural racism and injustice produces high levels of stress and burnout (Abresch et al, 2022 ). In recent years, addressing social determinants of health, including racism, has become a core part of the field of Maternal and Child Health (MCH), which serves vulnerable populations in sensitive developmental periods, and often addresses system inequities to achieve health goals (Pies & Kotelchuck, 2014 ; Rosario et al, 2022 ).…”
Section: Purposementioning
confidence: 99%
“…One important source of stress in work is emotional labor, which occurs when work requires the management of personal emotions for effective job performance, or to meet workplace norms and goals (Hammonds & Cadge, 2014 ; Załuski & Makara-Studzińska, 2018 ). A growing body of research has found high levels of emotional labor and burnout, and a dearth of workplace supports among public health and healthcare workers (Abresch et al, 2022 ; de Beaumont, 2017 ; Yeh et al, 2020 ).…”
Section: Purposementioning
confidence: 99%
See 2 more Smart Citations